The effect of pH and dissolved organic carbon on the growth kinetics of Ac. cupricumulans JTC3 and L. ferriphilum HT pertinent to the BIOX® process - Maritz, Leo (Department of Chemical Engineering, 2022)
The BIOX® process was designed to pre-treat refractory gold-bearing concentrates to enable gold recovery. It, and related, processes are well accepted commercially. An iron- and sulfur-oxidizing microbial consortium provide lixiviants for dissolution of mineral sulfides. The autotrophic iron-oxidizing bacterium, Leptospirillum ferriphilum HT, has been regarded as the dominant iron-oxidizer within the BIOX® culture since establishing this technology in the mid-1980s; however recent studies of the BIOX® consortia present in commercial BIOX® plants worldwide revealed a dominant presence of heterotrophically-inclined archaea including the iron-oxidizer, Acidiplasma cupricumulans JTC3. In this study, the effect of physicochemical factors, such as pH and temperature, and the presence of dissolved organic carbon on the growth and ferrous iron oxidation kinetics of these two microorganisms were investigated as potential driving forces behind the compositional shift in the BIOX® consortia. Biokinetic performance of L. ferriphilum HT-dominant and Ac. cupricumulans JTC3-dominant batch cultures were investigated using a basal salt media supplemented with 10 g.L-1 ferrous iron. Yeast extract was supplied as organic substrate for the archaeon. Growth curves were constructed from cultivation in ThomsonTM 24-well microtitre plates, measuring microbial growth by direct cell counting and ferrous iron concentration by the spectrophotometric 1-10 phenanthroline assay. Biokinetic performance of L. ferriphilum HT was investigated at the lower (40°C) and upper (45°C) temperature ranges typical of the BIOX® plant operating window and compared against the performance of Ac. cupricumulans JTC3 at 45°C, as a function of pH in the range pH 0.7-1.7. The effect of dissolved organic carbon on L. ferriphilum HT was assessed by spiking cultures with either yeast extract (0.1-0.5 g.L-1), 10-50% spent Ac. cupricumulans JTC3 culture filtrate or 1-30 mg.L-1 glycolic acid, acetic acid or pyruvic acid. The influence of organic carbon on Ac. cupricumulans JTC3 was investigated in a similar fashion by cultivating it in yeast extract, spent L. ferriphilum culture filtrate and in cultures spiked with 1-30 mg.L-1 glycolic acid, acetic acid and pyruvic acid. The biokinetic performance of the L. ferriphilum HT decreased substantially at 45°C and the detrimental effect of elevated temperature was exacerbated at pH < 1.3. Conversely, the highest Ac. cupricumulans JTC3 growth and volumetric oxidation rates were determined at pH < 1.3 and decreased with increasing pH. Considering the effect of organic compounds, complete inhibition of L. ferriphilum HT was observed in 0.5 g.L-1 yeast extract, 25% spent culture filtrate (0.079 g.L-1 DOC) and cultures spiked with 30 mg.L-1 glycolic acid, and 10 mg.L-1 acetic and pyruvic acid. No growth of Ac. cupricumulans JTC3 was observed in cultures lacking organic substrate or in cultures supplemented with only spent L. ferriphilum culture filtrate. Complete inhibition was observed in cultures grown in 50% spent culture filtrate supplemented with yeast extract. The contrasting effect of acid stress at pH < 1.5 on these two microorganisms at 45°C may contribute to the compositional shift observed in the archaeal-dominant BIOX® reactors whereas the effect of dissolved organic carbon (DOC) on these two microorganisms emphasizes the importance of microbial diversity in establishing robust biomining processes and the symbiotic relationship between organic-sensitive chemolithotrophs and their heterotrophic counterparts within the microbial consortia.